Estimation of Dietary Sodium Bicarbonate Dose Limit in Broiler under High Ambient Temperatures - Yunzhi Peng; Yongwei Wang; Dong Ning; Yuming Guo (The Journal of Poultry Science, 2013)
A six-week trial was conducted to estimate the dose limit of sodium bicarbonate (SB) in the diet of broiler chickens exposed to high ambient temperature. The estimation of SB dose limit was based on the growth performance, blood biochemical parameters and histological observation of the renal tissues of chickens. A total of 450 day-old male broilers were randomly distributed to five groups with SB supplemented at levels of 0 (control), 0.5%, 1.0%, 2.0% and 4.0%. The minimum and maximum average ambient temperatures were 26.4°C and 32.5°C, respectively, with relative humidity ranging from 57.2% to 83.8%. Results showed that (1) A linear effect of increasing dietary SB level was observed on body weight gain (BWG) (P<0.05), feed intake (FI) (P<0.05) and feed to gain ratio (F:G) (P<0.05) from day 1 to 21 and day 1 to 42. Supplementation of 4.0% SB decreased BWG (P<0.001) and FI (P<0.001), but increased F: G (P<0.001) from day 1 to 21, and decreased FI (P<0.001) from day 1 to 42. (2) Compared with the control treatment, an SB of 4.0% gave higher incidences of diarrhea (P<0.001), mortality (P<0.001) and ascites related mortality (P<0.001). (3) Rectal temperatures were linearly decreased (P<0.05) with rising SB levels. (4) Blood biochemical analysis indicated that SB higher than 1.0% decreased blood hemoglobin (HGB) (P<0.001), and increased hematocrit (HCT) (P<0.001) and serum malondialdehyde (MDA) concentration (P<0.001) on day 21. (5) Microscopic examination revealed that significant renal haemorrhage appeared when SB exceeded 1.0% and tubular dilation was observed in 4.0% SB treatment. In summary, dietary supplementation of 4.0% SB resulted in poor growth performance and higher mortality. In addition, SB higher than 1.0% affected blood biochemical parameters and caused renal lesions. The current results suggest that the dose limit of dietary SB is less than 1.0% for broilers under high ambient temperatures.